PENGARUH MOTIVASI, BONUS DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT OLSERA PRATAMA INDONESIA - Kelvin; Hikmah (SCIENTIA JOURNAL, 2022)
Along with the development of the times, companies are now more and more found in the community. With the increasing number of these companies, the company's competitors will also increase. If the company does not manage the company's management properly, then the company's goals will be difficult to achieve. By conducting research at PT Olsera Pratama Indonesia, the research aims to reveal the effect of motivation, bonuses and training on employee productivity in the company. This study uses primary data in proving the hypothesis. Data was collected by filling out questionnaires and interviews conducted at the Human Resource department of PT Olsera Pratama Indonesia. The prepared questionnaire was distributed to 137 respondents. Data processing and data testing were carried out using the SPSS version 25 application. Data analysis consisted of validity tests, reliability tests, classical assumption tests and influence tests. The classical assumption test itself consists of normality test, multicollinearity test and heteroscedasticity test, while the influence test consists of multiple linear regression test and coefficient of determination test. From the results of the study it was proven that employee motivation, bonuses and training had a significant positive effect on employee work productivity, either partially or simultaneously.